Pharmacotherapy of distal polyneuropathies in vibration disease - E. Yu. Radoutskaya; Ya. I. Onishchuk; I. I. Novikova (Лечащий Врач)
The article is devoted to an urgent medical and social problem - vibration disease, which occupies an important place in the clinic of occupational pathology. Syndromic classification of vibrational disease of the last revision is given. Particular attention is paid to the pharmacotherapy of neuropathic manifestations of the disease. The data of a 4-year clinical study of the effectiveness of a complex preparation, which includes trifosadenine, cocarboxylase, cyanocobalamin and nicotinamide, alpha-lipoic acid preparations in patients with professional vegetative-sensory polyneuropathy of the extremities, with an assessment of the state of motor, sensory and autonomic fibers by the method electromyography. In the study of motor fibers, the following were analyzed: the amplitude of the motor response (M-response), the speed of the impulse. For sensitive fibers, the speed of impulse conduction, distal latency, and amplitude of the sensory response (S-response) were determined. During the study, it was taken into account that the complex preparation, which includes triphosadenine, cocarboxylase, cyanocobalamin and nicotinamide, and lipoic acid affect different links in the etiopathogenesis of distal polyneuropathy, and the therapeutic effect is achieved in various ways. Analysis of the clinical picture of the disease revealed that most patients had sensory and vegetative disorders of the distal parts of the upper and lower extremities, spreading proximally. Practically, all the studied patients suffered from all types of sensitivity: vibration, temperature, pain and tactile. During the study, no side effects were observed, and all patients showed good tolerability of the drugs. The conclusion is made about the clinical efficacy of the complex drug, the possibility of its use as monotherapy, as well as complex therapy (with the use of lipoic acid) for neuropathic pain syndrome associated with peripheral polyneuropathy of occupational origin. The use of a complex preparation, which includes triphosadenine, cocarboxylase, cyanocobalamin and nicotinamide, allows you to reduce the dose of the concomitant drug with an analgesic effect, or cancel it. The drug, especially when used with alpha-lipoic acid preparations, can be recommended as a metabolic agent that improves the trophic function of peripheral nerve axons in patients with vibration disease for the long-term treatment of polyneuropathy of the upper and lower extremities.